The role of seals in coastal hunter-gatherer lifeways at Robberg, South Africa - Richardson, Leesha (Department of Archaeology, 2021)
Seals were a major dietary item for coastal hunter-gatherers and herders in South Africa. At Nelson Bay Cave (NBC), more than half of the Holocene mammal bones are from Cape Fur seals (Arctocephalus pusillus). Previous analyses of the seal assemblage from this site have studied only selected skeletal elements. This study is the first comprehensive analysis of seal remains from selected archaeological levels at Nelson Bay Cave and from the 2007/2008 excavations at nearby Hoffmans/Robberg Cave (HRC). Body part representation and frequency, age distribution and bone modification have been documented to determine the role of seals in the lifeways of hunter-gatherers and pastoralists at Robberg throughout the Holocene. The age profiles indicate that seals were obtained directly from a breeding colony throughout the Holocene. A breeding colony at Robberg would have been a rich and reliable resource for coastal foragers throughout the year. There were differences in skeletal element representation in the Early and Middle Holocene, compared with the Late Holocene. Axial skeletal elements are under-represented in earlier time periods, probably due to field butchery and the return of only parts of the seals to the living sites. In the Late Holocene, entire animals were taken back to site. Within each time period, the skeletal profiles of juveniles and adults indicate that both were processed similarly suggesting that aspects such as carcass size, weight and foraging distance were less important factors in transport decisions than the terrain of the Robberg Peninsula and the size of the hunting party. A large proportion of the bones were complete, or almost complete. There was little evidence of canid gnawing. The skeletal element representation, frequency and cut mark patterns suggest that the heads and flippers were highly sought after throughout the Holocene, as recorded in Arctic ethnography. Seals were also of spiritual significance, possibly in aiding transitions from the material into the spirit world.